Taciturnity in Native American Etiquette: A Cree Case - Darnell, Regna (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1981)
Ethnographers of speaking have distorted the realities of communicative events in native American societies by focusing exclusively on speech. The Cree of northern Alberta, along with many other native peoples, place far greater emphasis on the use of silence and on pause between turns at talk. Listening, rather than speaking, is the highly valued communicative skill. Lack of understanding of different communicative Systems is responsible for considerable inter-ethnic conflict.